Hubungan Antara Gaya Kelekatan dengan Interaksi Parasosial pada Penggemar K-POP - Pipit Nopiyanti; Anniez Rachmawati Musslifah; Faqih Purnomosidi (Concept: Journal of Social Humanities and Education, 2025)
This study examines the relationship between attachment styles and parasocial interaction among K-pop fans, where fans may develop an emotional bond with their idols despite the lack of real reciprocity. Attachment styles influence the level of attachment, with individuals with an anxious attachment style tending to be more emotionally involved and dependent on their idols, while those with an avoidant attachment style maintain more emotional distance. The role of social media in reinforcing the illusion of closeness is also a key focus of this study. The research aims to identify the relationship between attachment styles and parasocial interaction using a quantitative method with a correlation analysis approach. The findings indicate that fans with an anxious attachment style tend to have a more intense emotional bond, actively participate in fandom activities, and are more prone to anxiety when they lack updates about their idols. In contrast, those with an avoidant attachment style still consume idol-related content but with lower emotional involvement. The theoretical implication of this study supports the theories of attachment styles and parasocial interaction, explaining how emotional relationships form between fans and idols. Practically, this study can be used to develop digital literacy programs for K-pop fans to help them manage parasocial relationships in a healthier way, especially for individuals who are more vulnerable to excessive emotional attachment.